Pemulihan gizi buruk rawat jalan dapat memperbaiki asupan energi dan status gizi pada anak usia di bawah tiga tahun - Arnelia Arnelia; Astuti Lamid; Rika Rachmawati (Jurnal Gizi Klinik Indonesia, 2011)
Background: New approaches for the management of severe malnutrition such as outpatient rehabilitation complement the existing WHO inpatient protocols.Objective: The objectives of this study was to assess the improvement of energy intake as well as the nutritional status of severe malnourished children during comprehensive outpatient rehabilitation.Method: This study was conducted among severe malnourished children treated as outpatient rehabilitation at Nutrition Clinic at Center of Food and Nutrition Research and Development (CFNRD) in Bogor Indonesia. The design of the study was one group pretest-posttest design and recruitment of sample was taken from health centers in Bogor District. The criteria of sample was severe acute malnutrition based on weight for height Z score (WHZ) < -3 or, having clinical sign and aged under three years old. During a-six-months-comprehensive rehabilitation, the treatment was performed including: treatment of infectious diseases, nutrition and health education, psychosocial stimulation, formula-milk and supplementary feeding. WHO formula-milk was provided as F-75 and F-100 and supplementary feeding was given such as blended food, biscuit.Results: From a total of 26 severely malnourished children were selected, 24 children included in the analysis, 1 child was died 1 child was dropout. It was found that the average energy intake in baseline was 82 + 15 kcal/kg body weight/day.  After 1 month and 3 months intervention, average energy intake increased signifcantly to 121 + 13 kcal/kgBW/day and to 148 + 21 kcal/kg BW/day, respectively (p<0.000). Nutritional status increased from WHZ score of -3.56 + 0.71 at baseline, became -2.35 + 0.69 and -1.87 + 0.85 after 1 month and 3 months intervention. The proportion of normal child based on weight for height category were 50% after 3 months and 73.9% at the end of out patient rehabilitation. Conclusion: The comprehensive outpatient rehabilitation could significantly improve the energy intake and the nutritional status of severe malnourished children under three years of age.